1976
DOI: 10.3758/bf03214032
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic extinction of a conditioned taste aversion in rats

Abstract: The existence of a sexual dimorphism in the extinction of conditioned taste aversions in both fluid-deprived and nondeprived rats was investigated. When nondeprived rats were poisoned with LiCI after consuming a sucrose solution, males extinguished the subsequent conditioned taste aversion more slowly than females. There was no difference in the rate of extinction of a LiCI-induced conditioned taste aversion in fluid-deprived rats. Using marihuana extract distillate as the toxin, it was shown that the dimorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
32
2

Year Published

1978
1978
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 22 publications
10
32
2
Order By: Relevance
“…Female rats show superior passive avoidance performance--e.g, suppression ratio---when ongoing operant behavior is suppressed by the presence of aversion stimulation [ 10,18]. Conversely, female rats display inferior passive avoidance behavior when the retention of the response is not measured immediately after the aversive experience [5,6,9,17]. The present observations agree with these studies.…”
Section: Discussionsupporting
confidence: 82%
“…Female rats show superior passive avoidance performance--e.g, suppression ratio---when ongoing operant behavior is suppressed by the presence of aversion stimulation [ 10,18]. Conversely, female rats display inferior passive avoidance behavior when the retention of the response is not measured immediately after the aversive experience [5,6,9,17]. The present observations agree with these studies.…”
Section: Discussionsupporting
confidence: 82%
“…The comparatively rapid extinction of female as compared with male R. r. mindanensis confirms the previously reported sex differences in extinction for R. norvegicus (Chambers & Sengstake, 1976;Sengstake, Chambers, & Thrower, 1978). The sex difference was most apparent with RS and to a lesser degree with Cycle, Toxicity data for RS tested with Norway and Bandicota rats indicate females to be 1.5 to 5 times more sensitive than males (Brooks & Htun, 1980).…”
Section: Methodssupporting
confidence: 75%
“…These results were related to previous work showing that the rate of extinction of a conditioned taste aversion is dependent on levels of testosterone. Chambers and Sengstake (1976) have found that males extinguish a conditioned taste aversion more slowly than females. This sexual dimorphism has been shown to be concurrently dependent on testosterone (Chambers, 1976).…”
mentioning
confidence: 99%